Optimization of BAZNAS Programs on Sustainable Development Goals (SDGs): Analytic Network Process Approach (ANP) - Mohamad Handi Khalifah; Mohammad Soleh Nurzaman; Muhammad Cholil Nafis (International Journal of Zakat, 2017)
With the release of the United Nations (UN) Sustainable Development Goals (SDGs) program, the Government of Indonesia (BAPPENAS) is committed to realizing Sustainable Development Goals (SDG) in Indonesia. The essence of the spirit of Islam in solving poverty is the inclusive nature that must be attached to the development of Islamic finance and related to issues of poverty alleviation as a basic responsibility in achieving the goals of Shari’ah (al maqashid Shari’ah). In realizing Sustainable Development Goals (SDGs), it will require Zakat Organizational Programs. The purpose of this study is to measure the priority scale of the 7 Grand Programs of BAZNAS on 17 Goals of Sustainable Development Goals (SDGs). This research uses Analytical Network Process (ANP) method, wherein the process performs pairwise comparison and uses super matrix calculations to measure the interrelationship between the elements. The results of the measurements by Analytical Network Process (ANP) and statistics show some of the priority conclusions which include Pillars of Environmental Development (W= 0.47783), Partnership for All Development Objectives (W= 0.00486) and Zakat Community Development (W=0.07367). Keywords: Zakat Program, Sustainable Development Goals, Optimization, Development